A Longitudinal Intervention Study to Reduce Aggression by Children Ages 4-11 - V.J. Basso Robert; W. Graham John (Journal of Behavior Therapy And Mental Health, 2016)
Our objective was the early identification, assessment and treatment of aggression by primary school children four to eleven years old, with the goal of preventing school expulsion. The children were identified by teachers and other professionals for their aggressive behavior. Children were assessed for five symptoms which are linked to the development and persistence of social and/or physical aggressive behaviors: inattention, hyperactivity, anxiety, poor social functioning, and oppositional behavior. Long term follow-up continued for up to 9 years. Conners’ Scales for parents and teachers were used to assess the severity of predisposing symptoms and emotional lability. The children were treated with psychosocial and pharmacological interventions by social workers and a physician, in addition to utilizing community and school resources. Teachers reported a reduction in some of the predisposing symptoms: hyperactivity, emotional lability, oppositionality, and improved social functioning. Parents reported improvements in all five of the children’s physically aggressive behaviors. Early intervention for children’s aggressive behaviors was found to be effective. None of the children in the study were expelled from school.
Keywords: Childhood Aggression